The penalty and lagrange multiplier methods in the frictional 3d beam-to-beam contact problem = Metody współczynnika kary i mnożników Lagrange'a w zagadnieniu kontaktu z tarciem między belkami - Litewka, Przemysław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper is concerned with the frictional contact between beams. The purpose is to compare the results obtained by the penalty and Lagrange multiplier methods. The advantages and disadvantages of both methods are generally known and widely discussed but not in the quantitative manner and not specifically for the problem of beam-to-beam contact. The paper sketches briefly both formulations pointing out the main differences and features of both methods. The section with examples presents several cases of analysed beam-to-beam contact scenarios. The accuracy of results is taken into account, also the comparison to the full 3D analysis performed using the program ABAQUS is made. The computation times and the length of the codes for both methods are compared as well. These criteria allow one to conclude that for the beam-to-beam contact problem the Lagrange multiplier method is more attractive than the penalty method.
Keywords: belki; tarcie; metoda współczynnika kary; metoda mnożników Lagrange'a; beam-to-beam contact; Coulomb friction; penalty parameter method; Lagrange multiplier method